ANALISIS MODAL KERJA DAN TENAGA KERJA TERHADAP PENDAPATAN UMKM SENTRA WISATA KULINER KECAMATAN GENTENG KOTA SURABAYA - Ramadani, Gilang; Sitohang, Arga Christian (Nirta Learning Centre, 2024)
The culinary industry in Indonesia has experienced rapid development, becoming one of the main sub-sectors in the creative industry. The industrial sector plays an important role in the Indonesian economy because the industrial sector can increase foreign exchange for the country. The culinary industry is one of the sectors that is growing rapidly in Indonesia, especially in big cities such as Surabaya. Working capital and labor are two key factors that have a major influence on the income of the culinary industry. This can be realized through regional culinary tourism that has an impact on tourist satisfaction when visiting an area. Although the potential for growth in the culinary industry is very large, business actors face various challenges, such as tight competition and changes in consumer tastes. It is important for UMKM actors to optimize the use of working capital and maximize the potential of labor to increase income. The purpose of this study is to analyze the simultaneous influence of working capital and labor on the income of UMKM Culinary Tourism Center in Genteng District, Surabaya City. The type of research that will be conducted is quantitative research with a descriptive approach, namely a case study at the Culinary Tourism Center, Genteng District, Surabaya City. The approach used in the study is descriptive. This study uses quantitative data. This study uses primary data sources obtained through interviews (questionnaires) with business actors and secondary data obtained from data sources that are not directly obtained from the Surabaya City Cooperatives, Small and Medium Enterprises and Trade Service and the Surabaya City RENSTRA. This sampling uses purposive sampling. The sample population is 60 traders at the Culinary Tourism Center, Genteng District. The analysis technique uses multiple linear regression analysis.The results of the research and discussion can be concluded that Working capital and labor have a simultaneous effect on the income of UMKM Culinary Tourism Center, Genteng District, Surabaya City..